Newborn body composition and child cardiovascular risk markers: a prospective multi-ethnic Asian cohort study. (30th July 2022) - Ong, Yi Ying; Tint, Mya-Thway; Aris, Izzuddin M; Yuan, Wen Lun; Chen, Ling-Wei; Fortier, Marielle V; Choo, Jonathan; Ling, Lieng Hsi; Shek, Lynette; Tan, Kok Hian; Gluckman, Peter D; Yap, Fabian; et al.
Abstract: Background: Early epidemiological studies have associated low birthweight with increased cardiovascular risk. We aimed to examine whether the fat and fat-free components of birthweight have differing relationships with childhood cardiovascular risk markers. Methods: In the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort, air displacement plethysmography was conducted within 24 h after delivery in 290 naturally conceived singletons. We investigated associations of newborn cohort-specific standardized z-score of fat mass, fat-free mass, body fat percentage and birthweight on child (at 6 years of age) carotid intima-media thickness, pulse wave velocity, blood pressure, prehypertension/hypertension (>110/70 mmHg) and standardized systolic and diastolic blood pressure (SBP and DBP) trajectories (at 3–6 years of age), taking account of maternal education, height, tobacco exposure, parity, ethnicity, child's sex, gestational age, age at follow-up, and other maternal factors. Results: Clear inverse associations were seen for blood pressure with z-score of fat mass [SBP, β (95% CI): −1.31 mmHg (−2.57, −0.06); DBP: −0.79 mmHg (−1.74, 0.15)] and body fat percentage [SBP: −1.46 mmHg (−2.73, −0.19); DBP: −0.80 mmHg (−1.75, 0.16)], but not with fat-free mass [SBP: 0.27 mmHg (−1.29, 1.83)]; DBP: −0.14 mmHg (−1.30, 1.03)]. Being in the lowest tertile of fat mass or body fat percentage was associated with higher blood pressure trajectories and prehypertension/hypertension risk [OR (95% CI), fat mass: 4.23 (1.41, 12.68); body fat percentage: 3.22 (1.09, 9.53)] without concomitantly higher overweight/obesity risk. Conclusions: At birth, low adiposity was associated with increased childhood blood pressure. Low newborn adiposity might serve as a marker of poor fetal growth or suboptimal intrauterine conditions associated with hypertension risk later in life.